Nearinfrared spectral mapping of Titan's mountains and channels - Barnes, J.W.; Radebaugh, J.; Brown, R.H.; Wall, S.; Soderblum, L.; Lunine, J.; Buratti, B.J.; Baines, K.H.; Sotin, C.; Le Mouelic, S.; Rodriguez, S.; Clark, R.N.; et al. (Lunar and Planetary Institute, Houston, 2007)
Cassini studies of the surface of Titan are beginning to reveal its nature. In addition to hills, channels, and cobbles seen by the Huygens probe, the Visual and Infrared Mapping Spectrometer (VIMS) and RADAR instruments onboard the orbiter have seen sand dunes , channels , mountains [5, 6], and cryovolcanic candidates. Recently the RADAR team announced the discovery of possible lakes near Titan’s north pole.